AB1335 The clinicopathologic characteristics of granulomatosis with polyangiitis (wegener's): Retrospective study of 45 patients in korea. (23rd January 2014) - Kim, H.W.; Kim, J.W.; Im, C.H.; Shin, K.C.; Lee, E.Y.; Lee, E.B.; Song, Y.W.
Abstract : Background: The epidemiologic studies of granulomatosis with polyangiitis (Wegener's) (GPA) have been reported primarily in European/American countries while there are only a few data available from Asian area. Recent clinical studies from Japan and China indicated that there is a geographical difference in the incidence of GPA (1, 2) and the different ANCA pattern between Asian and Caucasian may be associated with different clinical manifestations. Objectives: The aim of this study is to anlayze the clinicopathologic characteristics of Korean patients with GPA. Methods: We retrospectively reviewed 45 patients with GPA regarding clinical manifestations including histology, positivity of ANCA, categorization of disease stages, disease activity states in a single tertiary referral hospital. Patients were categorized into a predominant form based on immunopathologic scoring system of granulomatous-vasculitic activity (3). Results: Thirty-one patients (68.9%) showed ANCA positivity (C-ANCA/P-ANCA, 44.4%/20.0%, proteinase-3 (PR3) ANCA/myeloperoxidase (MPO) ANCA, 48.4%/16.1%). ANCA positive patients (female 29.6%) were associated with higher frequency of renal involvement (51.6% vs 7.1%, p=0.004), elevated serum creatinine (29.0% vs 0%, p=0.018) and higher mortality (29% vs 7.1%, p=0.041) compared with ANCA negative patients. Thirty-three patients (73.3%, female 60.6%) were categorized into a granulomatous form, whereas vasculitic form and mixed form were found in 8.9% and 17.8% respectively. Age at diagnosis were younger (51.2 vs 62.3, p=0.045), and initial remission rate (69.7% vs 25.0%) and the relapse rate (60.8% vs 0%) were higher in granulomatous form compared with vasculitic form. Conclusions: Taken together, in Korean patients with GPA, ANCA positivity was found in 68.9% and associated with renal involvement and higher mortality. The granulomatous form was predominant. References: Fujimoto S, Watts RA, Kobayashi S, Suzuki K, Jayne DR, Scott DGet al. Comparison of the epidemiology of anti-neutrophil cytoplasmic antibody-associated vasculitis between Japan and the U.K. Rheumatology (Oxford).2011;50:1916-20. Chen M, Yu F, Zhang Y, Zou WZ, Zhao MH, Wang HY. Characteristics of Chinese patients with Wegener's granulomatosis with anti-myeloperoxidase autoantibodies. Kidney Int. 2005; 68: 2225-29. Pierrot-Deseilligny Despujol C, Pouchot J, Pagnoux C, Coste J, Guillevin L. Predictors at diagnosis of a first Wegener's granulomatosis relapse after obtaining complete remission. Rheumatol. 2010;49: 2181-90. Disclosure of Interest: None Declared